A Meta-Analysis Approach on Medical, Surgical and Expectant Management on Abortion of First Trimester (Epidemiology, Biostatistics, and Public Health, 2024)
An increase in miscarriage in the first trimester of gestation and its associated complication is burden-some on the quality of life of a woman. Medical, surgical, and expectant care are carried out after the miscarriage to remove any remaining tissues in the uterus. Understanding the efficacy and safety of these interventions will raise awareness and be a deciding factor to choose an appropriate treatment plan. Present review aims to determine the efficacy and safety of medical, surgical, and expectant care of various medical and surgical methods for first-trimester miscarriage. This review included studies that allocated women to medical, surgical or expectant management in the first trimester. PubMed, Cochrane Library, MEDLINE, and Embase Library were searched for the literature. The primary outcome was the complete evacuation of products of conception. Data were independently reviewed, graded for evidence quality, and assessed for risk bias by using the guidelines of PRISMA (Preferred Report Items for Systematic Review and Meta-Analysis). 21 eligible articles were included in this systematic review, comprising of 7931 patients undergoing medical, surgical or expectant-management for early spontaneous-miscarriage. The success rate in surgical intervention was higher when compared with medical intervention (OR: 16.12 [9.11, 28.52]) and expectant management (OR: 2.78 [2.13, 3.61]). Whereas medical intervention had a high success rate when compared with expectant-management (OR: 4.29 [2.31, 7.97]). The review determines the effect of medical, surgical, and expectant-management procedures on women who have had spontaneous-miscarriages in their first-trimester. PROSPERO-International prospective register of systematic reviews–CRD42020154395.
Keywords: surgery; medical; Expectant management; Spontaneous Abortion; First trimester; Systematic review